Chaucer's Miller's, Reeve's, and Cook's Tales : An Annotated Bibliography 1900-1992 - Greentree, Rosemary; Burton, T. L.; Biggs, David (Book collections on Project MUSE., 1997)
An annotated bibliography describing editing and critical works on three of Chaucer's tales. The authors make extensive use of the standard bibliographies of English literature, medieval studies, and Chaucerian studies.